Aplikasi 1-Methylcyclopropene untuk Meningkatkan Vase life Bunga Potong Zingiber spectabile Griff. Silvana - Juang Gema Kartika; Tiara Adyantari (Indonesian Society for Horticulture / Department of Agronomy and Horticulture, 2014)
ABSTRACTThe freshness of Zingiber spectabile Griff Silvana (bihip) as cut flowers must be maintained by the appropriate post-harvest treatment. One of the post-harvest technologies that is commonly used is the use of chemical 1-Methylcyclopropene (1-MCP). This study was aimed to extend the vase life of bihip flowers using 1-MCP to gain optimum concentration of 1-MCP that can extend the vase life of bihip flowers, and to find the best application technique of 1-MCP for longest vase life of bihip flowers. This study used a completely randomized design (CRD) factorial with two factors. The first factor was the concentration of 1-MCP that consists of five levels; 0 ppm (A0), 0.001 ppm (A1), 0.002 ppm (A2), 0.003 ppm (A3), and 0.004 ppm (A4). The second factor was application technique of 1-MCP : sprayed (B1) and soaked (B2). The results showed that 1-MCP significantly extended the vase life of cut flowers bihip flowers up to 11.30 day compared to control which was only 9.55 day. Concentration 0.004 ppm of 1-MCP was able to extend optimum vase life of cut flowers bihip until 11.30 day. Method of 1-MCP application to efficiently extend bihip flowers until 11.10 day was soaking in a solution of 1-MCP. The combination treatment of 1-MCP to extend the vase life of bihip flowers was 1-MCP treatment concentration of 0.004 ppm and soaking treatment. Treatment with 1-MCP at 0.004 ppm extended bihip flowers vase life.Key words: 1-Methylcyclopropene, bihip flowers, vase life, Zingiber spectabile Griff. Silvana ABSTRAKBunga potong Zingiber spectabile Griff. Silvana (bihip) perlu dipertahankan kesegarannya dengan cara perlakuan pasca panen yang tepat. Salah satu teknologi pasca panen adalah penggunaan bahan kimia 1-Methylcyclopropene (1-MCP). Penelitian ini bertujuan untuk memperpanjang vase life bunga bihip dengan menggunakan 1-MCP, mendapatkan konsentrasi 1-MCP optimum yang dapat memperpanjang vase life bunga bihip, dan mencari cara aplikasi yang efisien untuk memperpanjang vase life bunga bihip. Penelitian ini menggunakan rancangan acak lengkap (RAL) Faktorial dengan 2 faktor yaitu konsentrasi 1-MCP dan metoda aplikasi 1-MCP. Konsentrasi 1-MCP terdiri dari lima taraf: 0 ppm (A0), 0.001 ppm (A1), 0.002 ppm (A2), 0.003 ppm (A3), dan 0.004ppm (A4). Caraaplikasi 1-MCP terdiri atas dua taraf: disemprot (B1) dan direndam (B2). Hasil penelitian menunjukkan bahwa 1-MCP secara nyata dapat memperpanjang vase life bunga potong bihip hingga mencapai 11.30 hari dibandingkan dengan tanpa perlakuan 1-MCP yaitu hanya 9.55 hari. Konsentrasi 1-MCP yang optimum untuk memperpanjang vase life bunga potong bihip hingga 11.30 hari yaitu dengan konsentrasi 0.004 ppm. Cara aplikasi 1-MCP yang efisien untuk memperpanjang bunga bihip hingga 11.10 hari yaitu dengan cara merendam bunga dalam larutan 1-MCP. Kombinasi perlakuan 1-MCP yang dapat memperpanjang vase life bunga bihip yaitu perlakuan 1-MCP konsentrasi 0.004 ppm dengan cara aplikasi direndam.Kata kunci: 1-Methylcyclopropene, bihip, vase life, Zingiber spectabile Griff. Silvana